Gut Microbiota in Celiac Disease: Is There Any Role for Probiotics? - Pecora, Francesco; Persico, Federica; Gismondi, Pierpacifico; Fornaroli, Fabiola; Iuliano, Silvia; de'Angelis, Gian Luigi; Esposito, Susanna (Frontiers in Immunology, 2020)
Celiac disease (CD) is an immune-mediated disorder initiated by the ingestion of gluten in genetically predisposed individuals. Recent data shows that changes in the gut microbiome composition and function are linked with chronic inflammatory diseases; this might also be the case for CD. The main aim of this manuscript is to discuss our present knowledge of the relationships between gut microbiota alterations and CD and to understand if there is any role for probiotics in CD therapy. PubMed was used to search for all of the studies published from November 2009 to November 2019 using key words such as “Celiac Disease” and “Microbiota” (306 articles), “Celiac Disease” and “Gastrointestinal Microbiome” (139), and “Probiotics” and “Celiac Disease” (97 articles). The search was limited to articles published in English that provided evidence-based data. Literature analysis showed that the gut microbiota has a well-established role in gluten metabolism, in modulating the immune response and in regulating the permeability of the intestinal barrier. Promising studies suggest a possible role of probiotics in treating and/or preventing CD. Nevertheless, human trials on the subject are still scarce and lack homogeneity. A possible role was documented for probiotics in improving CD-related symptoms, modulating the peripheral immune response and altering the faecal microbiota, although the results were not consistent in all of the studies. No evidence was found that probiotic administration might prevent CD onset. Knowledge of the role of intestinal bacteria in the development of CD opens new possibilities for its treatment through probiotic administration, even though further studies are needed to better clarify whether probiotics can help treat or prevent the disease and to define which probiotics to use, at what dose and for how long.